Transobturator slings for female stress urinary incontinence - Sousa, A (2019)
Stress urinary incontinence affects about 20-40% of women. Treatment with transobturator mid-urethral slings is consensually accepted nowadays. The goal of this study was to evaluate the success rate and most frequent complications of surgical treatment with transobturator mid-urethral slings in stress urinary incontinence.